Photoperiod-sensitivity genes shape floret development in wheat - Perez Gianmarco, Thomas (2019)
Lengthening the pre-anthesis period of stem elongation (or late-reproductive phase, LRP) through altering photoperiod sensitivity has been suggested as a potential means to increase the number of fertile florets at anthesis (NFF) in wheat. However, little is known about the effects that the Ppd-1 genes modulating plant response to photoperiod may have on reproductive development. Here, five genotypes with either sensitive (b) or insensitive (a) alleles were grown in chambers under contrasting photoperiods (12 h or 16 h) to assess their effects. The genotypes consisted of the control cultivar Paragon (three Ppd-1b) and four near-isogenic lines of Paragon with Ppd-1a alleles introgressed from: Chinese Spring (Ppd-B1a), GS-100 (Ppd-A1a), Sonora 64 (Ppd-D1a), and Triple Insensitive (three Ppd-1a). Under a 12-h photoperiod, NFF in the genotypes followed the order three Ppd-1b > Ppd-B1a > Ppd-A1a > Ppd-D1a > three Ppd-1a. Under a 16-h photoperiod the differences were milder, but three Ppd-1b still had a greater NFF than the rest. As Ppd-1a alleles shortened the LRP, spikes were lighter and the NFF decreased. The results demonstrated for the first time that Ppd-1a decreases the maximum number of florets initiated through shortening the floret initiation phase, and this partially explained the variations in NFF. The most important impact of Ppd-1a alleles, however, was related to a reduction in survival of floret primordia, which resulted in the lower NFF. These findings reinforce the idea that an increased duration of the LRP, achieved through photoperiod sensitivity, would be useful for increasing wheat yield potential.